Protective organic coatings (ASM Handbook ;, 2015)
Text "is comprised of five divisions, which offer introductory material, an in-depth presentation of specific coating materials, practical information on surface preparation and coating application, coverage of coating use by various industries, and detailed discussion of coating analysis and evaluation methods."--Page iii.